The “PROMETHEUS” European Project: Gdańsk Fortress Route (Poland) - Daniele Bursich; Sandro Parrinello (Proceedings)
Starting in 2018, the PROMETHEUS H2020 project has been involved in the establishment of analysis methodologies for Cultural Heritage Routes (CHR) associated with historical architectural heritage. The project’s research activities have primarily focused on examining various itineraries, ranging from the regional scale of Russian churches in Upper Kama located in Perm (Russia), to the provincial scale encompassing sites related to James I of Aragon’s conquest in the Kingdom of Valencia (Spain), and finally to the urban scale encompassing fortifications in the city of Gdansk (Poland). Throughout the project’s duration, digital technologies have been employed and tested to create archives and information systems that aim to devise storytelling strategies for defining, representing, and promoting these routes. This endeavor involves the collaboration of more than 35 researchers from three European countries, who are implementing interdisciplinary synergistic actions to develop knowledge-driven approaches and formulate effective designs for digitally narrating intricate architectures.